Mit dyplomacji pingpongowej w świetle przyszłych prób wykorzystania sportu w celu kreacji zbliżenia międzynarodowego - Kobierecki, Michał Marcin (W kręgu wyobrażeń zbiorowych. Polityka, władza, społeczeństwo, 2019)
The aim of the article is to investigate the ways of using sport in order to shape international brand of a state. Accordingly, various forms of shaping state’s international image with the use of sports diplomacy have been analyzed and shortly described – within the proposed typology. An attempt to verify a hypothesis concerning sports diplomacy as a significant tool of shaping state’s international brand was also made. Badanie zostało sfinansowane przez Narodowe Centrum Nauki w ramach projektu nr 2015/19/D/HS5/00513.